Ten-year review of peripheral lymphadenopathy in tertiary hospital in South Western Nigeria (2016)
Peripheral lymphadenopathy is a common clinical presentation in Nigeria, and there have been many studies published on it from different parts of the country. This study is to provide an update on the clinicopathological pattern of lymphadenopathy in Ibadan. Methods: Lymph node biopsies received at the Department of Pathology, University College Hospital, Ibadan, Nigeria from January st 2003 to December 31st 2012 were reviewed. Special stains and immunohistochemistry were also applied. Results: 429 cases,251 females and 178 in males were studied. Modal age group was in the sixth decade. The mean age of females (41.4 years) was significantly greater than that of males (34.5 years), p=0.000. Commonest sites were axillary (31.5%) and neck groups (24%), with axillary nodes more often involved in females and neck group of nodes more often involved in males. Metastatic cancer and reactive hyperplasia were the commonest diseases. Males more frequently had non-specific hyperplasia (34.3%) and non-Hodgkin lymphoma (23.6%), while females more often had metastasis (45.4%) and non specific hyperplasia (19.1%). Patients with metastatic cancer had the highest mean age of 46.5 years, followed by those with malignant lymphomas and reactive hyperplasia. Conclusion: Primary and metastatic malignancies are common causes of lymphadenopathy in this environment. The use of selective immunohistochemical antibody panels is advocated for proper diagnosis of malignant lesions of the lymph node.